HARDENING OF CASTINGS AT FREE FORMING OF INTERNAL SURFACE - E. I. Marukovich; V. F. Bevza; V. P. Grusha (Литьë и металлургия)
The reasons of arising of the hollow castings polythickness at free forming of internal surface are investigated. The recommendations on its reduction are given